Temporal But Not Spatial Gait Parameters Associated With Lower Balance Capacity in Moderate-High Functioning Persons With Stroke. Issue 4 (6th October 2021) - Handelzalts, Shirley; Steinberg-Henn, Flavia; Farquhar, Jenna; Shkedy Rabani, Anat; Levy, Sigal; Riemer, Raziel; Soroker, Nachum; Melzer, Itshak
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and purpose: Falls are a major health concern after stroke. Spatial and temporal gait asymmetry and variability can contribute to instability and increased fall risk in persons with stroke (PwS). We aimed to quantify gait spatiotemporal symmetry and variability parameters in PwS undergoing rehabilitation in the subacute stage of the disease, by comparison to healthy participants, and to examine the associations between these parameters and patients' reactive and proactive balance capacity. Methods: Twenty-two PwS and 12 healthy adults walked over a computerized treadmill system at their self-selected walking speed. Symmetry and variability of gait parameters (step length, swing time, and stance time) as well as upper extremity and lower extremity angular range of motion in the sagittal plane were extracted. In addition, the Berg Balance Scale (BBS) and the fall threshold in response to sudden surface translations at increasing intensities were assessed. Results: PwS demonstrated significantly higher asymmetry in all gait parameters in comparison to controls. Also, PwS demonstrated increased stance time variability in comparison to healthy controls and increased swing time variability in the paretic lower extremity. Significant negative associations were found between fall threshold and stance time asymmetry in PwS ( r = −0.48, P = 0.022), between the BBS and swing time asymmetry ( r = −0.50, P = 0.018), and between the BBS and stance time variability of the paretic lower extremity ( r = −0.56, P = 0.006). Discussion and Conclusions: Findings highlight the importance of gait temporal symmetry and variability measures for dynamic balance control after stroke. These parameters should be considered when assessing gait recovery and safety in PwS. Video Abstract available for more insight from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A355 ).